Nanotechnology-Based Cosmeceuticals for Anti-Aging and Skin Regeneration - Chetna Chhabra; Rohit Saroha; Muneeb Kosvi; Gauri Mudgal (Recent Trends in Cosmetics, 2026)
Nanotechnology has transformed the cosmetic industry of the cosmeceuticals by allowing the production of sophisticated delivery systems that improve the stability, penetration, bioavailability, and therapeutic efficacy of active ingredients in cosmetics. The present review identifies the value of nanotechnology-based cosmeceuticals in anti-aging and skin regeneration, with special focus on the recent developments in nanocarrier technologies and their use in dermatology. Many nanocarriers have exhibited great potentials in enhancing delivery of antioxidants, vitamins, peptides, growth factors, and botanical extracts to deeper skin layers which include liposomes, niosomes, solid–lipid nanoparticles, nanostructured lipid carriers, polymeric nanoparticles and nanoemulsions. These systems have demonstrated to offer control release, improved skin permeation, and safeguard of delicate bioactive compounds against degradation, which improves anti-aging activity and regenerative results. Formulations based on nanotechnology have been demonstrated to induce collagen production, decrease oxidative stress, promote wound healing, tissue healing, and enhance skin wellbeing. Recent clinical research and commercial trends suggest that nano-enabled cosmeceuticals have a better performance than conventional formulations in wrinkle reduction, skin hydration, skin elasticity, and photoprotection. Future developments in skin care include the emergence of novel innovations that are likely to change the landscape of the skin care, including the use of personalized nano-cosmeceuticals, artificial intelligence-based formulation design, smart nanocarriers, and targeted delivery systems. Nevertheless, with all this progress, issues surrounding the safety, toxicology testing, regulatory standards, scalability in manufacturing and quality control of nanoparticles are still key factors to consider. Overall, nanotechnology is a fast-growing platform that has enormous potential in terms of improving anti-aging therapy and skin regeneration by more effective, safer, and personalized dermatological treatment
Keywords: Anti-aging; Cosmeceuticals; Nanocarriers; nanotechnology; skin regeneration